The effect of different ratios of zeolite content in the phosphate-bonded investment on surface roughness and dimensional change of the casting - (:unkn) unknown (Trans Tech Publications Ltd, 2007)
In this study, 2.5-10 weight % natural zeolite (clinoptilolite) was added into phosphate bonded- investment in consideration of its molecular sieve property. Before casting, thicknesses of specimens were measured in 50 × magnifying stereo microscope. Average surface roughness (Ra) was measured. The first group was assigned as control and no zeolite addition was performed. In the second group, 2.5%, in the third group 5%, in the fourth group 7.5% and in the fifth group 10% zeolite by weight was added to investment powder. According to our study, volumetric increase was determined in each group. The highest increase was observed in the second group with 1.87%. The lowest one was observed in the fifth group with 1.03%. The lowest surface roughness was determined in the second group with 4.41 μm. Although surface roughness and volumetric change values demonstrated differences, the change between groups could not reach statistical significance. It can be concluded that zeolite can be added to phosphate-bonded investment in order to decrease surface roughness and dimensional change of casting.
Keywords: Casting; Clinoptilolite; Dimensional change; Investment; Surface roughness; Zeolite